2005
DOI: 10.3748/wjg.v11.i16.2371
|View full text |Cite
|
Sign up to set email alerts
|

Radical induction theory of ulcerative colitis

Abstract: To propose a new pathogenesis called Radical Induction to explain the genesis and progression of ulcerative colitis (UC). UC is an inflammatory bowel disease. Colonic inflammation in UC is mediated by a buildup of white blood cells (WBCs) within the colonic mucosal lining; however, to date there is no answer for why WBCs initially enter the colonic mucosa to begin with. A new pathogenesis termed "Radical Induction Theory" is proposed to explain this and states that excess un-neutralized hydrogen peroxide, prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
187
0
20

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(220 citation statements)
references
References 127 publications
3
187
0
20
Order By: Relevance
“…Rupture of this defense system allows the migration of intestinal lumen bacteria into the sterile layers of colon wall. In an attempt to fight against bacterial infiltration, inflammatory cells migrate from the systemic circulation, promoting and keeping the inflammatory system that characterizes the disease 21 . Neutrophil infiltration causes increased production of OFRs, which further aggravates the epithelium harm 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rupture of this defense system allows the migration of intestinal lumen bacteria into the sterile layers of colon wall. In an attempt to fight against bacterial infiltration, inflammatory cells migrate from the systemic circulation, promoting and keeping the inflammatory system that characterizes the disease 21 . Neutrophil infiltration causes increased production of OFRs, which further aggravates the epithelium harm 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The resulting oxidative stress causes histological and biochemical alterations similar to those found in experimental models of chemically induced colitis or human colitis. The oxidative stress causes alterations in the colonic mucosa that aggravate according to the time of diversion [20][21][22][23][24][25][26][27] . Based on these evidences, the use of substances with antioxidant activity was suggested to be effective in the prevention and treatment of this disease 20,27 .The benefits of these substances in the treatment of DC were recently confirmed with the application of enemas with 5-aminosalicylic acid (5-ASA), a powerful antioxidant, was demonstrated to reduce the levels of tissue oxidative stress and improve the inflammatory process in the mucosa without fecal stream, even after the ex-vivo exposure to hydrogen peroxide (H 2 O 2 ) 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the importance of the role of reactive oxygen species (ROS) in the etiopathogenesis of ulcerative colitis and other inflammatory diseases that affect the colon mucosa, such as DC, has increased 13,16,17,18,19 . Likewise, experimental studies have confirmed the role of ROS in the development of chemically induced colitis by acetic acid, TNBS and DSS 20,21,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…The tissue damage to the colonic mucosa has been attributed to the large capacity of the activated neutrophils to produce ROS 16,19 . Tissue fragments collected from patients with ulcerative colitis showed greater activity in lipid peroxidation levels compared to normal tissue 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The immune barrier and physical barrier are made up of the immune cells, and epithelial cells and tight junction (TJ) complex, respectively [5]. It was reported that disturbance of the intestinal mucosal immune system of fish results in an impaired immune response leading to pathogen translocation, infection and inflammatory bowel diseases [5,6]. Therefore, maintaining the intestinal mucosal immune barrier function is of utmost importance for fish [5].…”
Section: Introductionmentioning
confidence: 99%